Step-by-step explanation:
f(x) = 4x-5
g(x) = 2x
(f + g)(x)=f(x) +g(x)=4x-5+2x=6x-5
Answer:The value of the given function is 6
Step-by-step explanation:
Given the following expression 3*f(-4)-3*g(-2), to find the values, we can assume that;
f(-4) = 10g(-2) = 8
Substitute the given parameters into the expression to have:
3*f(-4)-3*g(-2)
= 3((10) - 3(8)
= 30 - 24
= 6
Answer:
If solving for x then it's x
=
4
y
If solving for y then it's y=x/4
Step-by-step explanation:
With the given information you can form a system of equations with the help of the formular for the nth term of an arithmetic sequence. From which you find the first term and the common difference, with which you can wite the recursive formula for the sequence.
Answer:
3x+8
Step-by-step explanation:
linear function formula ax+b
when x=3 3a+b=17 and when x=6 6a+b=26
3a=9 a=3,
when x=3 3.3+b=17 9+b=17 b=8
3x+8